Subantarctic Mode Water variability influenced by mesoscale eddies south of Tasmania - Herraiz-borreguero, Laura; Rintoul, Stephen R. (Journal of Geophysical Research, 2010)
Subantarctic Mode Water (SAMW) is formed by deep mixing on the equatorward side of the Antarctic Circumpolar Current. The subduction and export of SAMW from the Southern Ocean play an important role in global heat, freshwater, carbon, and nutrient budgets. However, the formation process and variability of SAMW remain poorly understood, largely because of a lack of observations. To determine the temporal variability of SAMW in the Australian sector of the Southern Ocean, we used a 15 year time series of repeat expendable bathythermograph sections from 1993 to 2007, seven repeat conductivity-temperature-depth sections from 1991 to 2001, and sea surface height maps. The mean temperature of the SAMW lies between 8.5 degrees C and 9.5 degrees C (mean of 8.8 degrees C, standard deviation of 0.3 degrees C), and there is no evidence of a trend over the 18 year record. However, the temperature, salinity, and pycnostad strength of the SAMW can change abruptly from section to section. In addition, the SAMW pool on a single section often consists of two or more modes with distinct temperature, salinity, and vertical homogeneity characteristics but similar density. We show that the multiple types of mode water can be explained by the advection of anomalous water from eddies and meanders of the fronts bounding the Subantarctic Zone and by recirculation of SAMW of different ages. Our results suggest that infrequently repeated sections can potentially produce misleading results because of aliasing of high interannual variability.